Spatiotemporal variation of the carbon footprint of tobacco production from 2004 to 2017 in China - Zheng, Yu; Qin, Yanqing; Duan, Weidong; Dong, Wenshuai; Zhang, Xi; Yin, Guangting; Li, Changgen; Song, Zonghao; Xie, Liangwen; Zhan, Lei; Ti, Jinsong (Frontiers in Environmental Science, 2024)
Tobacco, as a significant cash crop in China, warrants a comprehensive investigation into the spatiotemporal dynamics of its carbon footprint in order to address greenhouse gas (GHG) emissions and foster low-carbon, environmentally friendly agricultural practices. Employing the life cycle assessment (LCA) methodology, this study aims to scrutinize the temporal variations in the carbon footprint across different functional units of tobacco production in China from 2004 to 2017, thereby elucidating its composition and key influencing factors. The findings reveal that the average carbon footprint per unit area and per unit yield of tobacco production in China during the aforementioned period amounted to 4098.99 kg CO2-eq•ha -1 and 1.97 kg CO2-eq•kg -1 , respectively, exhibiting an upward trend over time. Notably, fertilizer and agricultural films emerged as the primary sources of greenhouse gas emissions in Chinese tobacco production, accounting for 26.63% and 24.54% of the total emissions, respectively. Remarkably divergent carbon footprints were observed among various provinces in China. Specifically, Jiangxi, Hunan, and Guangdong exhibited the highest carbon footprints per unit area, with values of 4908.65 kg CO2eq•ha -1 , 4852.90 kg CO2-eq•ha -1 and 4833.56 kg CO2-eq•ha -1 , respectively. Likewise, Jiangxi, Fujian, and Yunnan recorded the highest carbon footprints per unit yield, reaching 2.31 kg CO2-eq•kg -1 , 2.23 kg CO2-eq•kg -1 and 2.22 kg CO2-eq•kg -1 , respectively. Conversely, Inner Mongolia, Hebei, Jilin, and Heilongjiang exhibited lower carbon footprints per unit area, namely 3952.06 kg CO2-eq•ha -1 , 3751.08 kg CO2-eq•ha -1 , 2935.81 kg CO2-eq•ha -1 , 3264.83 kg CO2-eq•ha -1 and 2830.92 kg CO2eq•ha -1 , respectively. Moreover, these regions displayed both high yield and productivity. This investigation highlights the significance of implementing measures such as scientific fertilization, reducing agricultural film usage, and expediting the mechanization process of tobacco cultivation to foster the development of an environmentally sustainable tobacco industry in China.